Loss of bone morphogenetic protein-binding endothelial regulator causes insulin resistance - Hua Mao (Nature Portfolio, 2021)
Type 2 diabetes is associated with chronic inflammation and is characterized by insulin resistance. Here, the authors identify a crucial role for endothelial BMPER function in glucose homeostasis, and BMPER overexpression was shown to alleviate insulin resistance and hyperglycemia in diabetic mice.